Telepractice-delivered communication training for informal caregivers of people with aphasia: A pilot study. - Anjum, Javad; Husak, Ryan S.; Kudrna, Laynee (International Journal of Speech-Language Pathology, 2025)
Purpose: To establish proof of concept of a student-led, telepractice-delivered communication partner training towards enhancing communication between people with aphasia and their informal caregivers in everyday conversations. Method: Two dyads were recruited, each consisting of a person with aphasia and their caregiver. A pre-training questionnaire was completed by caregivers, followed by a weekly communication training session delivered by graduate student clinicians via telepractice to each dyad over 12 weeks. The caregivers then completed a post-training questionnaire. Both questionnaires included 13 Likert-scale questions and one open-ended question requiring an extended response. Result: Pre- to post-training improvements for both dyads were identified on two domains of the questionnaire: (a) frustrations of the caregiver and person with aphasia and (b) caregivers' knowledge and confidence in using communication strategies. This quantitative data was supported by additional extended responses regarding informal caregivers' current communication strategies when communicating with the person with aphasia. Conclusion: Both informal caregivers reported integrating communication strategies learned as part of the training in their interactions with the person with aphasia and experiencing fewer communication breakdowns during the two weeks following the training. The pilot study offers proof of concept for incorporating telepractice-delivered caregiver communication training as part of aphasia rehabilitation.